Risk factor assessment and outcome analysis in elderly (≥60 years) patients of severe head injury - Gopal, N. N.; Kumar, Ashish; Singh, Amit Kumar; Dubey, Saurabh Anand (International Surgery Journal, 2020)
Background: Incidence of head injuries is rising all over the world. Only few studies have been performed regarding severe head injury in elderly people. We aimed to study the epidemiology, mode of injury, management, co-morbidity, associated injuries which affects the outcomes. Severe head injury is unconsciousness >6 hours and GCS 3-8. In India 6.63% of the total population above 60 years is considered elderly. Falls are the major contributor to TBI in elderly but in India RTA is still the main contributor. Outcomes of TBI, both in terms of mortality and function, are significantly worse in the elderly. Methods: Objective of this study was to find the risk factors affecting the outcome in severe head injury. This was a prospective study and carried on 56 patient in Department of surgery of M. L. N. Medical College, Prayagraj from September 2018 to September 2019. Results: Male were most commonly affected but the gender had no significant prognostic effect on outcome. RTA were the most common cause of head injury. GCS at admission was directly related to outcome. Bilateral non-reactive pupils had poor outcome. Type of hematoma and midline shift had also affected the outcome. Operated cases had better outcome than non-operated cases. Any associated injury with TBI had worsened the outcome in patient. Any co-morbid condition associated with brain injury had slower recovery and worsen the outcome. Overall mortality in this series was 64.28% and unfavourable outcome was 76.79%. Conclusions: Severe head injury in elderly people had worst outcome.